Limberg flap versus primary closure in the treatment of pilonidal sinus: a randomised clinical study - M., Devaprashanth; M., Srinivas N.; N., Akhihlandeshwari (International Surgery Journal, 2021)
Background: Pilonidal sinus is a chronic disease usually involving the sacrococcygeal area. Various treatment modalities exist, yet few comparison studies exist to compare the efficacy of one modality over the other. Hence this randomized clinical study was undertaken as an attempt to compare the outcomes of pilonidal sinus following Limberg flap procedure and primary closure. Methods: 60 patients undergoing surgery for pilonidal sinus disease were considered for the study. 30 patients underwent excision and primary closure and 30 patients underwent Limberg flap repair. They were followed up for 1 year. Duration of hospital stay, duration of inability to work, postoperative infection, wound dehiscence, and postoperative recurrence in a follow up period were recorded. Descriptive statistics, chi- square tests and independent t-test are the statistical tools employed. Results: Mean age was 29.83±4.99 years. Male:female ratio was 5.66:1. The mean duration of hospitalization in group A was significantly less (p<0.05) than group B. The patients in group B returned early to routine work (21.56±3.92 days) as compared to 30.5±5.92 days in group A (p<0.05). 5 of 30 patients in group A and 2 of 30 in group B developed surgical site infection. (p>0.05. 4 patients developed wound dehiscence in group A only which was found to be statistically significant. Conclusions: Limberg flap in treatment of pilonidal sinus is associated with shorter hospitalization, early return to routine work and less wound dehiscence as compared with excision and primary closure. Wound infections are comparable with both the modalities.